Antioxidants and lipid peroxidation status in the blood of patients with alopecia - Naziroglu, M; Kokcam, I (Wiley, 2000)
The aim of this research was to determine levels in blood of vitamin E, beta-carotene, lipid peroxidation as thiobarbituric-acid reactive substances (TBARS) and reduced glutathione (GSH) and activity of glutathione peroxidase (GSH-Px) in patients with alopecia. Studies were carried out on 37 patients with alopecia and 34 healthy age-matched controls. Red blood cell (RBC) and plasma samples from healthy and patient subjects were taken. Beta-carotene levels (P < 0.001) in plasma and levels of GSH (P < 0.05) and the activity of GSH-Px (P < 0.05, P < 0.001) in both plasma and RBC samples were significantly lower in patients with alopecia than in controls, whereas TBARS levels in plasma (P < 0.05) and RBC (P < 0.001) samples were significantly higher in patients with alopecia than in controls. However, vitamin E levels in plasma did not differ statistically. Although being far from conclusive, these results provide some evidence for a potential role of increased lipid peroxidation and decreased antioxidants in alopecia. Copyright (C) 2000 John Wiley & Sons, Ltd.
Keywords: alopecia; lipid peroxidation; antioxidants; vitamin E; beta carotene; skin